Propuestas para elevar la eficiencia en la gestión de inventarios en Protemax S.R.L. - Terrones Mestanza, Jonathan Maico (2021)
The objective of the following professional sufficiency work is to show how the application of different proposals for improvement in inventory management within a supply chain area can contribute significantly to the strategic objectives of a company. In this case, the improvements made between 2018 and 2019 in the automotive company Protemax S.R.L. To do this, an analysis has been made of the situation found at the beginning of the management and subsequently how, starting from a desired improvement situation, a series of measures were implemented, emphasizing demand planning, later changes were made in the management of purchases and supplies, fundamental steps to be able to have a positive result in the management of inventories. Modern concepts of strategic management and supply chain were applied, leaving behind the traditional concept of logistics area. We proceed with the strategic evaluation of the Canvas model, crossed SWOT, analysis of variable contribution margin, functional strategic map, implementation of policies and procedures, calculations of safety stock and key management indicators. Finally, based on the implementation of the aforementioned, the financial sustainability of the project presented in the following work is demonstrated, making conclusions and suggesting recommendations to continue with the strategic alignment of the area to the general strategic and respective control through indicators that have contributed and will contribute to the improvement of the contribution margin sought.